Development of magnesium oxychloride cement with enhanced water resistance by adding silica fume and hybrid fly ash-silica fume. (1st September 2021) - Guo, Yingying; Zhang, Y.X.; Soe, Khin; Wuhrer, Richard; Hutchison, Wayne D.; Timmers, Heiko
Abstract: In this paper, a water-resistant magnesium oxychloride cement (MOC), an environment friendly cementitious material, was developed by incorporating silica fume and the hybrid of silica fume and fly ash. The effects of these admixtures on the water repellence of MOC were investigated via comprehensive macroscopic physical and mechanical tests and micro-scale studies. A formula design of MOC blended with 15% silica fume and 15% fly ash retained the compressive strength as high as 100% and 95% after 28 days' and 56 days' immersion in water, respectively. Micro-scale studies, including XRD, FTIR, SEM, MIP, TG/DSC and XRM, were conducted to discover the mechanism of the enhanced water resistance of the new MOC. Besides, a clear and precise distribution of the hydration products in well-cured MOC specimens was demonstrated with the X-ray mapping (XRM) technique. It was found that adding silica fume or the hybrid of silica fume and fly ash optimised the porous structure of MOC and thereby increased the density and compressive strength leading to the enhanced water resistance. The filling effect of fine silica fume and fly ash particles, as well as the formation of Mg–Cl–Si–H gel, was found to be the main reason for the densified microstructure of MOC. The fractional contribution of phase 5, i.e. the main phase of MOC, decreased with the combined silica fume and fly ash, and this helped to relieve the internal stress and improve the stability of MOC, leading to enhanced water repellence. Highlights: A water-resistant environment friendly MOC was developed by adding industry by-products including silica fume and fly ash. 15% fly ash-15% silica fume-MOC retained 100% and 95% of compressive strength after 28 days' and 56 days' water immersion. The mechanism of increment in water resistance and mechanical strength was studied comprehensively by microscale studies. Results from microscale study agree and explain well with those from mechanical test. The research solved the notorious poor water resistance issue of MOC, which has restricted its wide application.